Cross-country ski - Carlsson, P.; Ainegren, M.; Tinnsten, M.; Sundström, D.; Esping, B.; Koptioug, A.; Bäckström, M. (The engineering approach to winter sports, 2016)
Cross-country skiing, biathlon and ski orienteering are competitive sports with practitioners who are mostly from countries in the northern hemisphere. The competition season is during the time when the ground is covered with snow, which roughly extends from mid-November to late March. During the rest time of the year, which is a long preparatory period of training for the skiers before the competition season, the skiers use roller skis for dryland training with the aim of imitating skiing on snow. Furthermore, over the last few decades, fairly specific indoor testing methods for cross-country skiers have become possible due to the development of treadmills that allow roller skiing using classical and freestyle techniques. Outdoor experiments on snow, using cross-country skiers, biathletes and skiorienteers, are difficult to standardize due to changes in factors that influence the grip and glide (static and dynamic friction coefficients) of the skis and the skier, and thus the skiing technique and energy expenditure. Such factors are air and snow temperature, humidity and snow and wind conditions. Also, it is difficult to control the intended speed and to find a track profile with proper, relatively constant, inclination for the specific core-technique during the time required to retrieve stable energy expenditure. Frictional forces play a critical role in the ski and snowboard gliding. The ambition to decrease friction and improve gliding efficiency strongly impacts the construction and design of the corresponding equipment. Despite significant progress in research into the gliding friction with snow and ice many of the critical issues still remain unresolved. Even though the system may seem rather simple the processes and interactions involved are quite complex. Significant variations of the environmental and dynamic conditions in skiing and snowboarding also complicate the analysis and modeling of the gliding friction phenomenon.